Tinjauan Yuridis Tentang Pengurangan Masa Pidana (Remisi) terhadap Tindak Pidana Narkotika - Ni Kadek Nilawati Dwi Cahya; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara (Jurnal Interpretasi Hukum, 2020)
Indonesia is a rule of law which gives relief to prisoners every year, referred to as remission, is a policy of the government in order to reduce criminal penalties for each suspect caught in criminal law. Remission is given to those who during the sentence meet the provisions as people who are entitled to remission as well-behaved, and comply with any applicable regulations at the place of punishment. For someone who during his sentence is always against the rules cannot be given a remission. This study aims to determine the regulation of reducing the criminal period and determine the provision of remissions for narcotics offenders. The research method used is a type of normative legal research conducted by the method of recording and assessment based on legal materials. Researchers study and gather information through legal science books without deviating from positive law in order to conclude a conclusion. The implementation of the remission for narcotics offenders, namely the determination of the remission, is carried out by the decision of the head of the regional office on behalf of the minister, after issuing the stipulation of the head of the regional office must submit a report on the determination of the reduction of the criminal period to the minister of the Ministry of Justice and Human Rights cq. Directorate General of Corrections.